Inverted battery design as ion generator for interfacing with biosystems - Chengwei Wang (Nature Portfolio, 2017)
At the molecular level, biological activities involve the transport of ions in a system. Here the authors demonstrate an ‘electron battery’ by inverting the configuration of a traditional Li-ion battery to generate an ionic current to interact with a biosystem for potential biomedical applications.